How have the state and the domestic firms in Singapore and Korea responded to corporate governance reforms? - Heng, Denise Shi Si. (2011)
After the Asian financial crisis in 1997, many Asian countries embarked on a search for the best corporate governance system. As newly industrialised nations in Asia, Singapore and Korea started almost on equal grounds in its corporate governance practices. But since then, as the countries adapted corporate governance practices to their own countries, we now see significant disparities between these two countries. This paper seeks to investigate this disparity during the convergence towards Anglo American CG standards. We will first look at how the states responded respectively to different pressures via the introduction of regulations and enforcement systems. Using case studies of companies in Singapore and Korea with similar ownership patterns, we conduct in-depth firm-level analysis, concentrating on the board structure. The assessment on firms‘ board effectiveness involves further investigations that put the true independence of independent directors in Singapore and Korea to test. Finally, a cross-national comparative analysis between Singapore and Korea is carried out to evaluate the extent and effects of convergence towards Anglo-American standards. We find that though the countries tried to emulate certain best practices in a board like emphasising the importance of the independent director, they were almost never able to achieve the same standard as counterparts in the West due to unique characteristics present in the country.